The Effect of Student Learning Styles and Learning Videos on the Learning Outcomes of Light Vehicle Engine System Subjects in Class XI TKR SMK N 1 Ratahan - Rottie, Max Marthen; Oroh, Rolly; Daud, Metsi; Rompas, Parabelem Tinno Dolf; Olii, Djami (Jurusan PTIK Universitas Negeri Manado, 2024)
ABSTRACT The low learning achievement of students in class XI TKR SMK Negeri 1 Ratahan in the subject of Light Vehicle Engine Systems is caused by several factors, such as: Learning Style, Motivation, Interest and the lack of teachers using Learning Media, such as Learning Videos, pictures etc. Based on this reason, research was conducted with the aim of knowing how much influence learning styles and the use of learning videos on learning outcomes and to find out whether there is an influence of learning styles and the use of learning videos in influencing student learning outcomes in Light Vehicle Engine System subjects. The population in this study were all Class XI TKR students who studied Light Vehicle Engine System Subjects as many as 60 students and samples for Variable (X1) as many as 60 students and samples for Variable (X2) as many as 60 students. Using quantitative research methods regression approach. The data collection technique uses a questionnaire with a Likert scale and uses the Education Report Value. Data processing using classical assumption tests: Multicollinearity test, Heteroscedasticity test: Data Validity and Reliability Test, Data Normality Test, Data Homogeneity Test, F Test, Differential Test (t test), analyzed using the IBM SPSS For Windows 25.0 Program. The results show that the effect of learning styles and the use of learning videos on learning outcomes is in the high category. Learning styles and the use of learning videos have a contribution to the influence on learning outcomes in the Light Vehicle Engine System Subject of Class XI TKR students by 43%. The conclusion with this research is that there is a positive and significant influence between learning styles and learning videos on the learning outcomes of light vehicle engine system subjects of class XI TKR students of SMK Negeri 1 Ratahan.